EFEKTIVITAS PENERAPAN SISTEM KEHADIRAN BERBASIS FINGERPRINT DALAM MENINGKATKAN DISIPLIN APARATUR SIPIL NEGARA PADA DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI MALUKU - Billy Jeremy Christiaan; Petronela Sahetapy; Jeanly Waisapy (CV. Adiba Aisha Amira, 2023)
This study uses a quantitative research method which aims to see how the Effectiveness of Implementing a Fingerprint-Based Attendance System in Improving State Civil Apparatus (ASN) Discipline in the Communication and Informatics Office of Maluku Province. The subjects in this study were 30 (N = 30) civil servants at the Communication and Informatics Office of Maluku Province. The analysis technique used is simple linear regression analysis. The results of this study indicate that (1) the effectiveness of the fingerprint- based attendance system (X) has a positive and less significant effect on the discipline of State Civil Apparatus (ASN) employees. This means that if the effectiveness of the fingerprint-based attendance system is higher, the discipline of the State Civil Apparatus (ASN) employees will increase.